Circulating tumor DNA analysis of EGFR-mutant non-small cell lung cancer patients receiving osimertinib following previous tyrosine kinase inhibitor treatment. (July 2020) - Beagan, Jamie J.; Bach, Sander; van Boerdonk, Robert A.; van Dijk, Erik; Thunnissen, Erik; van den Broek, Daan; Weiss, Janneke; Kazemier, Geert; Pegtel, D Michiel; Bahce, Idris; Ylstra, Bauke; Heideman, Daniëlle A.M.
Highlights: ctDNA testing of NSCLC patients with complex treatment history in clinical setting. A trend between ctDNA detection and progression under osimertinib in 2nd / 3rd line. Monitoring response with ctDNA may benefit patients following previous EGFR-TKIs. Abstract: Objectives: Circulating tumor (ct)DNA analysis is rapidly gaining acceptance as a diagnostic tool to guide clinical management of advanced non-small cell lung cancer (NSCLC). Clinically-actionable EGFR mutations can be detected in ctDNA before or after first-line EGFR-Tyrosine Kinase Inhibitor (TKI) treatment, but data are limited for patients with a complex treatment history. This study aimed to explore the feasibility of ctDNA testing in a clinical setting of NSCLC patients receiving osimertinib as a second or third line EGFR-TKI. Materials and Methods: Twenty EGFR T790M-positive NSCLC patients, who had received osimertinib as a second or third line EGFR-TKI and had donated blood samples while attending routine follow-up consultations between April and November 2016, were retrospectively selected to test plasma cfDNA for tumor-guided EGFR mutations. We used EGFR mutations previously identified in tumor-tissue to retrospectively test plasma ctDNA from 20 patients who had received osimertinib as a second or third line EGFR-TKI. Both EGFR-TKI sensitising and T790 M resistance mutations were analysed by droplet digital PCR (ddPCR) in plasma taken alongside routine consultations and ctDNA detection was correlated with response under osimertinib. Follow-up solid-tissue biopsies were obtained after disease progression. Results: CtDNA was detected under osimertinib treatment in four out of the eight patients (50 %) who showed no response, two out of the seven (29 %) who showed an initial response and none of the five patients (0 %) who showed an ongoing response. The fraction of EGFR -mutant ctDNA in plasma tended to be higher in non-responders (0.1–68 %), compared to the initial responders (0.2–1.1 %). Blood samples were donated up to 34, 27 and 49 weeks after the start of osimertinib for the non-, initial and ongoing responders, respectively. Conclusions: These findings support a potential role for ctDNA analysis in response monitoring of NSCLC patients with a complex EGFR-TKI treatment history. The weak trend between ctDNA detection and disease progression warrants larger studies to further investigate potential clinical utility.